Wizards don't wear graduation gowns - Dadey, Debbie; Jones, Marcia Thornton; Gurney, John Steven, 1962- (New York : Scholastic, 2002)
The Bailey School kids set out to discover whether the new assistant principal is really a wizard
O
"A Little Apple paperback."
b
b
Keywords: Assistant school principals -- Juvenile fiction; Wizards -- Fiction; Bailey School Kids (Fictitious characters) -- Fiction; Children's stories; Fantasy fiction